Brain Arteriovenous Malformation Recurrence After Apparent Microsurgical Cure: Increased Risk in Children Who Present With Arteriovenous Malformation Rupture. Issue 10 (October 2020) - Copelan, Alexander; Drocton, Gerald; Caton, M. Travis; Smith, Eric R.; Cooke, Daniel L.; Nelson, Jeffrey; Abla, Adib A.; Fox, Christine; Amans, Matthew R.; Dowd, Christopher F.; Halbach, Van V.; Higashida, Randall T.; et al.
Abstract : Background and Purpose: Do children have an increased risk for brain arteriovenous malformation (AVM) recurrence compared with adults and does this risk vary depending on initial presentation with AVM rupture? Methods: We retrospectively studied 115 patients initially presenting with brain AVM under age 25 years who underwent complete surgical resection of the AVM as documented by digital subtraction angiography (DSA) and had delayed follow-up DSA to evaluate for AVM recurrence after apparent initial cure. Results: The mean time from baseline DSA to follow-up DSA was 2.3 years, ranging from 0 to 15 years. Twelve patients (10.4% of the 115 patient cohort and 16.7% of 72 patients with hemorrhage at initial presentation) demonstrated AVM recurrence on follow-up DSA. All patients with recurrence initially presented with intracranial hemorrhage, and intracranial hemorrhage was a significant predictor of recurrence (log rank P =0.037). Among patients with initial hemorrhage, the 5-year recurrence rate was 17.8% (95% CI, 8.3%–35.7%). All recurrences occurred in patients who were children at the time of their initial presentation; the oldest was 15 years of age at the time of initial AVM surgery. The 5-year recurrence rate for children (0–18 years of age) with an initial presentation of hemorrhage was 21.4% (95% CI, 10.1%–41.9%). Using Cox regression, we found the risk of AVM recurrence decreased by 14% per each year increase in age at the time of initial surgical resection (hazard ratio=0.86 [95% CI, 0.75–0.99]; P =0.031). Conclusions: There is a high rate of recurrence of apparently cured brain AVMs in children who initially present with AVM rupture. Imaging follow-up is warranted to prevent re-rupture. Abstract : Supplemental Digital Content is available in the text.